Analisis Pengembangan Sistem Informasi Akuntansi Berbasis Microsoft Excel Dalam Meningkatkan Kualitas Laporan Keuangan Bumdes Sariwangi Raharja Printing - Putri, Melly Pertama; Afriady, Arif (Indonesian Accounting Research Journal, 2025)
BUMDes Sariwangi Raharja Printing is one of the village-owned enterprises that has implemented an accounting information system based on Microsoft Excel in preparing its financial reports. However, in its implementation, there are several issues that are considered to affect the quality of the financial reports, particularly regarding accuracy. Therefore, a study was conducted to analyze the existing accounting information system implementation and its development to improve the quality of the financial reports of the BUMDes. The research method used in this study is research and development with the ADDIE development model (Analyze, Design, Develop, Implement, and Evaluate), with data collection techniques in the form of interviews, observations, and documentation. The result of this research is the development of an accounting information system based on Microsoft Excel that is more effective in improving the quality of financial reports. The quality of financial reports refers to aspects of relevance, reliability, understandability, and comparability. In addition, this research also produced a financial reporting application for BUMDes, which will be implemented as a tool for recording financial transactions at BUMDes Sariwangi Raharja Printing.